Algebra B
posted by Nancy .
x^2  5/2x + 25/16 = 4 + 25/16
= (x5/4)^2 = 64/16 + 25/16
= (x5/4)^2 = 39/16
Would someone please explain how we arrived at
(x  5/4)^2 = 64/16 + 25/16 from
x^2  5/2x + 25/16 = 4 + 25/16
Thanks in advance for your help.

Which side (left or right) is puzzling?

The left, Thanks

OK,
(x5/4)^2
= (x5/4)(x5/4)
multiplying (remember FOILfirst, outer, inner, last)
= x^2 (5/4)(x)  (5/4)(x) + (5/4)^2
= x^2  (10/4)(x) + (5^2)/(4^2)
= x^2 (5/2)(x) + (25)/(16)
Does that help? 
Oh, reverse FOIL!
Thank you. 
You're welcome, but I am not sure what you mean by reverse FOIL.
First terms: x and x
Outer terms: x and 5/4
Inner terms: 5/4 and x
Last terms : 5/4 and 5/4
I just want to be sure you have a good understanding about the order. 
Yes, You explained it very well. Thanks for taking the time.

You are very welcome.